Efektivitas Pembelajaran Daring terhadap Prestasi Belajar Siswa Kelas XI IPA SMAN 4 Luwu pada Mata Pelajaran Biologi Selama Pandemi Covid-19 - Nur Muhajirah Yunus; Sukmawati Syam (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine the effectiveness of online learning on student achievement in class XI IPA SMAN 4 Luwu in Biology Subjects During the Covid-19 Pandemic. This type of research is descriptive quantitative research. The sample in this study were students of class XI IPA 2 and XI IPA 3 of SMAN 4 Luwu as many as 70 students. Methods of data collection in the form of a questionnaire (questionnaire) and documentation. The sampling technique used is simple random sampling technique. The data in this study were analyzed using quantitative descriptive analysis. The results showed that the level of effectiveness of online learning on student achievement was 11.43% which said it was effective and 88.57% said it was less effective. Therefore, it can be concluded that online learning is not effectively applied to Biology Subjects in class XI IPA SMAN 4 Luwu so this needs to be taken into consideration and input for teachers in the future.